Composition and propositions of Nari commission - Hasan, Md. Mahmudul (New Age, 2025)
The notion that Islam gives women half of what men inherit is imprecise. The religion gives sons a bigger share of inheritance, as they have to bear greater financial burdens; and it gives women more inheritance when they need more support. It is important to remember that Islamic inheritance law is based on equity, not equality.